El control interno y su incidencia en la gestión administrativa y contable de la empresa Belitex S.A, cantón Quevedo, periodo 2012 - Zambrano Párraga, Martha Cecilia (2015)
The present investigation focused on the incidence of internal control in the company belitex sa, its main objective to evaluate and identify the type of internal control should be applied in the listed company. in support of the importance of proper internal control in companies, we develop a theoretical framework that gives a general approach of various concepts to be applied on an evaluation of this type, and why a company should implement this method in different areas. in the perspective adopted here, we can say that a department that did not apply adequate internal controls, may run the risk of making deviations in their operations and of course the decisions will not be the most appropriate for their management and could even lead to a crisis operational, so you should take a series of consequences that harm the results of their activities. things being so, it is clear that these changes can be achieved by implementing and adapting internal controls, which will be able to safeguard and preserve the assets or other instruments of a department of a company. in the preceding chapters we present the methodology applicable to this type of investigation and the results thereof. we present the research to those departments that do not have an adequate system of internal control. which it is important, considering that the institutions have a continuous evolution so they need efficient and effective controls.